Android Based Fuel Calculation System Application On MV. Pacific Bulk - Prasetyono, FX. Mario Dwi; Hermanto, Andy Wahyu; Heriyawan, Mohammad Sapta (Universitas Dharma Wacana, 2024)
The work of calculating ship fuel for machinists can now be changed to automatic in the Android application . With this, work will be faster and more accurate. The aim of the research is to find out how to make applications and how the Android-based fuel calculation system works on MVs. Pacific Bulk. The method used is research and development and Bord and Gall development with 10 steps. The research results show that the use of Android applications in calculating fuel on MV. Pacific Bulk is very useful for making it easier and faster for machinists to calculate ship fuel. The design process for the Android-based fuel calculation application on the MV Pacific Bulk Ship was carried out using Android Studio as an Integrated Development Environment (IDE). It can be operated using an Android cellphone which will make it easier to calculate the remaining fuel on the MV. Pacific Bulk Ship